Ultrasound‐guided fine‐needle aspiration of a posterior neck dedifferentiated liposarcoma with MDM2 fluorescence in situ hybridization performed on a Pap‐stained smear. Issue 4 (31st July 2014) - Zreik, Riyam; Soyalp, Krystal; Ruiz, Steve; Ward, Russell; Dobin, Sheila; Chen, Xiangbai; Liu, Lina; Rao, Arundhati
<x xml:space="preserve">Abstract</x> Head and neck liposarcomas, while rare, tend to be subcutaneous and well‐differentiated. Dedifferentiated liposarcomas of the head and neck are exceedingly rare in the literature. We present a case of a dedifferentiated liposarcoma arising in the soft tissue of the posterior neck of an 86‐year‐old man and diagnosed by fine‐needle aspiration. Aspirate smears showed a dual population of atypical lipomatous and spindled cells. MDM2 (murine double minute 2) amplification was demonstrated on a Pap‐stained smear using fluorescence in situ hybridization (FISH). To the best of our knowledge, this is the first report of MDM2 FISH amplification in a liposarcoma performed on an aspirate smear. Diagn. Cytopathol. 2015;43:320–324. © 2014 Wiley Periodicals, Inc.